Enhancement of oxygen permeation fluxes of La0.6Sr0.4CoO3-dhollow fiber membrane via macrostructure modification and (La0.5Sr0.5)2CoO4+ddecoration - Han, N.; Meng, B.; Yang, N.; Sunarso, J.; Zhu, Z.; Liu, Shaomin (Elsevier, 2018)
© 2018 Institution of Chemical Engineers Oxygen-selective perovskite hollow fiber membrane can be used to obtain an effective oxygen separation from air at high temperature (above 700 °C) for large scale application. Here, we display that oxygen permeation fluxes of La 0.6 Sr 0.4 CoO 3 (LSC 113 ) hollow fiber membrane was enhanced by macrostructure modification and (La,Sr) 2 CoO 4 (LSC 214 ) surface decoration. By changing the cross-section macrostructure from sandwich structure (for LSC-a fiber) to asymmetric structure (for LSC-b fiber), the oxygen flux was improved by up to 3.6-fold. Applying porous LSC 214 decoration on LSC 113 furthermore enhanced the oxygen fluxes for LSC-a and LSC-b, by up to 6.8-fold and 1.9-fold, respectively.